Neuroplasticity and Neuroprotective Effect of Treadmill Training in the Chronic Mouse Model of Parkinson’s Disease - Ewelina Palasz; Wiktor Niewiadomski; Anna Gasiorowska; Anna Mietelska-Porowska; Grazyna Niewiadomska (Neural Plasticity)
Physical training confers protection to dopaminergic neurons in rodent models of parkinsonism produced by neurotoxins. The sparing effect of physical training on dopaminergic neurons can be tested with training applied during chronic MPTP treatment, while the neurorestorative effect when training is applied after completing such treatment. In this study, the effect of the onset of training respective to chronic MPTP treatment was specifically addressed. Three groups of mice were injected with 10 doses of MPTP (12.5 mg/kg/injection) over 5 weeks. The first group remained sedentary; the second one underwent early onset training, which started 1 week before commencing MPTP treatment, continued throughout 5 weeks of treatment and 4 weeks thereafter; the third group underwent late-onset training of the same length and intensity as the former group, except that it started immediately after the end of MPTP treatment. Two groups served as controls: a saline-injected group that remained sedentary and saline-injected group, which underwent the same training as the early and late-onset training groups. Both early and late-onset physical training saved almost all nigral and VTA dopaminergic neurons, prevented inflammatory response, and increased the BDNF and GDNF levels to a similar extent. From these results one may conclude that early and late-onset training schedules were equipotent in their neuroprotective effect and that the mechanism of neuroprotection was similar. The sparing effect of early onset training may be satisfactorily explained by assuming that the increased level of BDNF and GDNF prevented the degeneration of dopaminergic neurons. To explain a similar number of dopaminergic neurons detected at the end of the early and late-onset training, one should additionally assume that the former training schedule induced neurogenesis. Results of this study support the view that physical activity may be neuroprotective even at a more advanced stage of PD and justify starting physical activity at any point of the disease.